First-principles study on the temperature dependent elasticity and thermodynamical properties of thermoelectric material NiSbS. (December 2022) - Yang, Dingfeng; Chen, Shuling; Quan, Xuejun; Wang, Yaoqiong; Gong, Xiangnan; Li, Yuanyuan
Abstract: The mechanical properties are critical factors in designing thermoelectric devices. In this work, the electronic structure, temperature dependent elasticity and thermodynamical properties of thermoelectric material NiSbS were investigated via quasi-harmonic approximation. Electronic structure calculation suggests that it exhibits metallic behavior with a band characteristic similar with that of n-type heavily doped semiconductor. The temperature-dependent elastic constants follow a normal behavior where these values decrease with the increase of temperature, and satisfy the stability conditions. The thermodynamical calculations suggest that NiSbS has weak expansion. Our calculation predicts that NiSbS has good mechanical property in application of thermoelectric device. Graphical Abstract: NiSbS can be designed as thermoelectric device owing to its excellent mechanical property via DFT simulation. ga1